The Legal Treatment of Islamic Marriage Ceremonies. (31st July 2018) - Probert, Rebecca; Saleem, Shabana
Abstract: The extent and status of religious-only marriages in England and Wales has attracted considerable attention in recent years and generated a number of proposals for reform. Yet, any discussion of what the law should be needs to be grounded in a clear understanding of the existing framework, in order to assess what is currently problematic and what needs to change. This article accordingly analyses the scope for entering into a legally binding religious marriage or combining civil and religious elements, the consequences for the parties if the marriage does not comply with the law and the offences that may be committed by officiants in such cases. Against this background, it goes on to consider a number of options for reform.